Experimental seismic behaviour of wall-to-half-timbered wall connections - Moreira, Susana Maria Trindade (2012)
The out-of-plane failure mechanisms due to seismic action observed in masonry walls of historical buildings are, in many cases, a direct result of poor connections between structural elements, which are incapable of assuring proper load transmission. Therefore, the need to prevent its occurrence raises critical importance around their unstrengthened and strengthened behaviour. A typical example is the connection between external and internal walls or between walls and floors. The wall-to-half-timbered wall connections are representative of connections existent in ‘Pombalino’ and ‘Gaioleiro’ buildings, constructed during the post-earthquake (1755) reconstruction of downtown Lisbon. In order to better understand the seismic performance of masonry wall-to-half-timbered wall connections and to increase information found in literature, a series of 5 tests were carried out in representative real scale specimens in which injected anchors were installed in an irregular stone masonry wall in order to improve the seismic response of the connection. Monotonic and cyclic pull-out tests were performed on representative connections in order to assess their performance and allow their characterization. Parameters considered include: failure mode, hysteretic curve, strength degradation and total energy. The results contribute to the existent body of knowledge on the topic, by expanding the experimental database. For further development, the experimental data allows the calibration of representative numerical models, enabling parametric studies of material properties and formulation of backbone curves. This data allows idealized behaviour to be established and utilized for the construction of global building models.